Training and Retaining Physician‒Scientists in Dermatology: The German Perspective - Katharina Sies; Alexander H. Enk (Elsevier, 2022)
In an ideal setting, physician‒scientists combine clinical practice and knowledge with scientific curiosity and research in synergy. Li et al. address the current challenges regarding the rare breed of physician‒scientists in the United States-much similar to those faced in German dermatology departments. The authors discuss multiple angles to transform the so-called leaky pipeline into a streamline of dermatologists in science.